Different pathological response and histological features following neoadjuvant chemotherapy or chemo-immunotherapy in resected non-small cell lung cancer - Alì, Greta; Poma, Anello Marcello; Di Stefano, Iosè; Zirafa, Carmelina Cristina; Lenzini, Alessandra; Martinelli, Giulia; Romano, Gaetano; Chella, Antonio; Baldini, Editta; Melfi, Franca; Fontanini, Gabriella (Frontiers in Oncology, 2023)
Non-small cell lung cancer (NSCLC) is the leading cause of cancer incidence and mortality worldwide. Neoadjuvant chemo-immunotherapy has led to clinical benefits in resectable NSCLC in comparison to chemo-therapy alone. Major pathological response (MPR) and pathological complete response (pCR) have been used as surrogates of neoadjuvant therapy response and clinical outcomes. However, the factors affecting the pathological response are still controversial. Therefore, in this study we retrospectively examined MPR and pCR in two different cohorts of NSCLC patients, 14 treated by chemotherapy and 12 by chemo-immunotherapy in the neoadjuvant setting. In resected tumor specimens, different histological characteristics were evaluated: necrosis, fibrosis, inflammation, presence of organizing pneumonia, granuloma, cholesterol cleft, and reactive epithelial alterations. In addition, we evaluated how MPR impacts on event-free survival (EFS) and overall survival (OS). In a small group of patients treated by chemo-immunotherapy, a gene expression analysis of the Hippo pathway was performed both in preoperative biopsies and matched post-surgical specimens. We observed a better pathological response in the chemo-immunotherapy treated cohort: 6/12 patients (50.0%) achieved a MPR ≤10% and 1/12 (8.3%) achieved pCR both on primary tumor and on lymph nodes. On the contrary, no patient treated with chemotherapy alone achieved pCR or MPR ≤10%. A higher amount of stroma in the neoplastic bed was observed in patients treated with immuno-chemotherapy. Moreover, patients achieving better MPR (including pCR) had significantly improved overall survival (OS) and event-free survival (EFS). After neoadjuvant chemo-immunotherapy, residual tumors showed a remarkable upregulation of genes consistent with the activation of YAP/TAZ. Also, alternative checkpoint, such as CTLA-4, were enhanced. In conclusion, our findings showed that neoadjuvant chemo-immunotherapy treatment improves MPR and pCR thus resulting in better EFS and OS. Moreover, a combined treatment could induce different morphological and molecular changes in comparison to chemotherapy alone, thus giving new insights in the assessment of pathological response.